Navigating The Turbulence of The Indonesian Property Industry: Analyzing The Competitive Dynamics of The Property Agent Sector in Indonesia’s Jabodetabek Area - Nanda Riva'i, Bulan Pratama (Journal of International Conference Proceedings, 2025)
The aim of this study is to analyze the roles of trust, quality, image, customer satisfaction to increase purchase intention towards real estate company service. A quantitative method was applied in this study. The data for this study collected through online questionnaires form. By using purposive sampling and convenience sampling technique, the questionnaire filled up by 258 (valid respondents) of people who have use real estate service. In order to fulfill the goal of this study, an analysis was conducted utilizing SEM or Structural Equation Model for hypothesis testing using Smart PLS 3. The findings of this study shows that trust, quality, image, and customer satisfaction contributes to the increasing of purchase intention. The originality of this research is that it is the first research integrating trust, quality, image, customer satisfaction toward purchase intention of real estate company